Subjektivní teorie a jednání učitelů: vícečetná případová studie v kontextu profesního rozvoje učitelů - Koubek, Petr (Pedagogický výzkum v teorii a praxi, 2021)
Title in English: Teachers' Subjective Theories and Behaviour: A Multiple Case Study in the Context of Teachers' Professional Development. Subjective theories are relatively stable cognitive structures, which guide approach to the educational process. Thee monograph presents four cases of civics teachers with the aim to illustrate their subjective theories concerning the meaning and goal of the subject taught and the psycho-didactic transformation of these goals into realised opportunities for pupils' learning.